Retroanálise da ruptura do talude de montante da Barragem do Açu no final do período construtivo - Vilhete, Didoney Fernandes (2017)
Risks associated to dam failure are very high. Problems of instability involving these structures bring catastrophic consequences to the social comunity. The Açu dam is a geotechnical work with significant importance in the Northeast, mainly in Rio Grande do Norte state. It is the largest dam of the state and has gained prominence in national and international literature with the slice of the upstream slope at the end of its construction period. In cases of failure, back analysis is a reliable technique used to calculate the shear strength parameters of the soil in order to avoid similar cases to happen. Considering the evaluation of strength data available in the academic environment, this work had as purpose to analyze the failure occurred in order to obtain the average shear strength parameters of the black clayey material that constituted the Açu dam core before the accident. In the first stage of this work the slope stability of the dam was analyzed and in the second stage the deterministic and probabilistic back analysis was performed. These analyzes were performed in Slide 7.0 from Rocscience platform. The results showed that the slope would fail with strength parameters of the black silty clay in the saturated condition, with values of probability of failure ranging from 60 to 97% between the equilibrium limit methods used in the analyzes. It was also possible to define the possible average shear strength values of black silty clay and to establish the causes of the dam failure. The cohesion and the friction angle values obtained at the instant of failure in the deterministic back analysis for black silty clay were cu=47.1 kPa and ϕu=0º. For the probabilistic back analysis the cohesion and the friction angle values obtained were cu=33,8 kPa and ϕu=3,1º, with a probability of failure of 52,7%. Therefore, it is concluded that the Açu dam upstream slope failure occurred because of errors in the design and construction phase of the dam accompanied by the loss of soil strength due to the excess of poropressures generated during the construction.